The Growth and Development of the Malaysian media landscape in shaping media regulation. - Abdullah, Zulhamri; Sheikh Sagoff, Syed Agil; Hassan, Md Salleh (2011)

(untitled)
An increase in the demand of digital media and information communication technology in a borderless world has encouraged Malaysia to move to a new era of knowledge creation and fast-moving competitive advantages especially in the media sector. This phenomenon has blurred boundaries between the broadcasting and computing industries in terms of their roles, functions and economic scale. The new technological environment in Malaysia has resulted in conflicts and posed challenges to the country. It may affect the current regulatory media approach and technology acceptance in harmonizing digital intellectual property, market power, content values, and diversion of cultures. The purpose of this paper is to identify the mechanism, concepts, and implementation of self-regulation in the Malaysian media environment. In-depth interviews were conducted with informants who were responsible for practicing the Content Code. The primary regulatory reference for the study is the Communication Act 1998. The media industry players in this study are media organizations that are governed by the Communication and Multimedia Act 1998, and members of the Communication and Multimedia Content Forum (CMCF). The focus on self-regulation and its procedures is based on the Content Code developed by the Content Forum of the media industry. This study provides useful insights for analyzing the development of Malaysian legislation, cyber policies and the implementation and practices of Malaysian media players. This study helps to shed information on the relevance and usefulness of local legislations and policies to local media practitioners and industry.